Parents' Perceptions of Eye-Gaze Technology Use by Children With Complex Communication Needs - Masayko, Sandra; McGowan, Joy; Grampurohit, Namrata (American journal of speech-language pathology, 2024)
Some preschool students with complex communication needs explore eye-gaze computer technology (EGCT) and adopt computer-based augmentative and alternative communication (AAC). The objective of this study was to follow preschool explorers of EGCT who are now school aged to describe the children's use of technology and parents' perceptions of its utility for communication, participation, or leisure. Ten parents completed survey questions by Internet and phone and reported their perceptions of nine children's effectiveness in the use and acceptance of AAC and the support they received in implementing technology. The results are reported as a descriptive study. All children in this research continue to use AAC technology in school and most at home. Many children who tried and obtained EGCT while in preschool continue to use that technology. Most parents agreed that the children understood how to use the devices, which enhanced the children's communication, and that the parents received sufficient support. Most children were limited in their use of the devices for leisure and control of their environments. Computer-based AAC for school-aged children who trialed it when they were in preschool appears to be a powerful means for them to communicate and participate. However, the technology appears not to be used to its full capabilities to support the children's agency to control environments and to pursue leisure. Teams may want to consider how to support children in using their AAC devices to meet multiple needs. The study was limited by its small sample size and its descriptive nature. Additional research on this subject is needed.